2020
DOI: 10.3389/fnins.2020.572595
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Volume Measures of the Mammillary Bodies Between Mild Cognitively Impaired Patients and Healthy Controls

Abstract: Purpose: To investigate the baseline values and differences for susceptibility and volume of the mammillary bodies between mild cognitively impaired (MCI) patients and healthy controls (HCs), and further explore their differences in relation to gender, MCI subtypes and apolipoprotein E (APOE) genotypes. Methods: T1-weighted and multi-echo gradient echo imaging sequences were acquired on a 3T MR scanner to evaluate the T1W based volume and susceptibility differences in the mammillary body for 47 MCI and 47 HCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 75 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…45 Moreover, this region harbors the supramammillary nucleus, which could modulate memory function through its extensive connections to the hippocampus. 2 We also found a strong relationship between MMB volume and total memory, as well as episodic verbal memory, which extends findings form previous (animal) studies, 19,20 ,46 and highlights the role of the fornix-mammillary body circuit in regulating episodic memory function. 47 Notably, MMB volume was also related to processing speed in both datasets, which is in line with a recent clinical case-control study in children.…”
Section: Discussionsupporting
confidence: 88%
“…45 Moreover, this region harbors the supramammillary nucleus, which could modulate memory function through its extensive connections to the hippocampus. 2 We also found a strong relationship between MMB volume and total memory, as well as episodic verbal memory, which extends findings form previous (animal) studies, 19,20 ,46 and highlights the role of the fornix-mammillary body circuit in regulating episodic memory function. 47 Notably, MMB volume was also related to processing speed in both datasets, which is in line with a recent clinical case-control study in children.…”
Section: Discussionsupporting
confidence: 88%
“…Both post-mortem and MRI studies have previously reported larger MBs in males than females ( Bernstein et al, 2012 ; Jin et al, 2020 ; Sheedy et al, 1999 ); however, these studies did not correct for overall brain volume. In contrast, Raz et al did control for skull size and found no sex-related differences ( Raz et al, 1992 ).…”
Section: Discussionmentioning
confidence: 90%
“…To better understand the contribution of MB neuropathology in these diverse conditions, it is necessary to have a detailed structural knowledge of the MBs in normal populations. While normative data for the MBs has been reported for adults ( Raz et al, 1992 ), and older adults in particular ( Jin et al, 2020 ), the equivalent data for younger populations has not previously been available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, MB volumetric loss in mild to moderate AD has been described when compared with healthy controls (Callen et al, 2001), MCI and older people with a subjective cognitive decline (Copenhaver et al, 2006). Increased iron level in the right mammillary body with no apparent volumetric differences has been reported when comparing MCI and healthy controls (Jin et al, 2020). Substantial decrease in neuronal population and abbreviation in dendritic arbores have also been reported in early cases of AD using electron microscopy and silver impregnation techniques (Baloyannis et al, 2016).…”
Section: Mammillary Bodiesmentioning
confidence: 99%